2017
DOI: 10.31478/201703i
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Eating Behaviors of Health Professionals: A Registered Dietitian Nutritionist Perspective

Abstract: For health professionals, stress and eating often combine in unhealthy ways. The stress comes early in their training and lingers throughout their careers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Body image and weight are important concerns for RDs, and this field tends to attract individuals who are interested in food. Thus, there may be some relationship between personal beliefs, actions, or opinions, perceived success, and perception as a role model for patients among RDs 30. However, weight status (ie, individuals of a higher weight or a lower weight) would not be expected as a driver of alignment with the HAES approach because the main concept of HAES is being health-focused instead of being weight-focused 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body image and weight are important concerns for RDs, and this field tends to attract individuals who are interested in food. Thus, there may be some relationship between personal beliefs, actions, or opinions, perceived success, and perception as a role model for patients among RDs 30. However, weight status (ie, individuals of a higher weight or a lower weight) would not be expected as a driver of alignment with the HAES approach because the main concept of HAES is being health-focused instead of being weight-focused 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be some relationship between personal beliefs, actions, or opinions, perceived success, and perception as a role model for patients among RDs. 30 However, weight status (ie, individuals of a higher weight or a lower weight) would not be expected as a driver of alignment with the HAES approach because the main concept of HAES is being health-focused instead of being weightfocused. 1 A recent study of RDs found that those who work in weight management are using intuitive eating approaches more often than traditional weight management practices.…”
mentioning
confidence: 99%